2014
DOI: 10.1002/2013gl059114
|View full text |Cite
|
Sign up to set email alerts
|

Power law scaling of topographic depressions and their hydrologic connectivity

Abstract: Topographic depressions, areas of no lateral surface flow, are ubiquitous characteristics of the land surface that control many ecosystem and biogeochemical processes. High density of depressions increases the surface storage capacity, whereas lower depression density increases runoff, thus influencing soil moisture states, hydrologic connectivity, and the climate‐soil‐vegetation interactions. With the widespread availability of high‐resolution lidar‐based digital elevation model (lDEM) data, it is now possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 49 publications
7
65
0
Order By: Relevance
“…Negative feedbacks that induce regular patterning inhibit the development of features, limiting the prevalence of large features and thus truncating the distribution of feature sizes. As such, we predicted that wetland features in BICY will deviate from the power law scaling observed for wetland depressions where negative patterning feedbacks are absent (Le & Kumar, ; van Meter & Basu, ). Power law distributions of feature areas implies the action of scale invariant or fractal processes acting over many orders of magnitude (Brown et al, ; Scanlon et al, ) and would imply one dominant process of basin formation at all scales.…”
Section: Methodsmentioning
confidence: 93%
“…Negative feedbacks that induce regular patterning inhibit the development of features, limiting the prevalence of large features and thus truncating the distribution of feature sizes. As such, we predicted that wetland features in BICY will deviate from the power law scaling observed for wetland depressions where negative patterning feedbacks are absent (Le & Kumar, ; van Meter & Basu, ). Power law distributions of feature areas implies the action of scale invariant or fractal processes acting over many orders of magnitude (Brown et al, ; Scanlon et al, ) and would imply one dominant process of basin formation at all scales.…”
Section: Methodsmentioning
confidence: 93%
“…The elevations of wetland bottoms and divides are results of the regional topography of the landscape, and thus can be derived from DEM data (Bertassello, Rao, Jawitz, et al, ; Le & Kumar, ). The procedure starts by evaluating the flow direction for each cell, and if the cell has no neighbours with lower elevation, it is identified as a sink, representing the bottom, z B , of potential wetlands ( N p ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these conjunctive models are being coupled to vegetation-hydrology dynamics (Ivanov et al, 2008), solute transport (VanderKwaak and Sudicky, 1999;Weill et al, 2011), and land-surface and atmospheric models (Maxwell and Miller, 2005;Maxwell et al, 2007). However, existing models have not been applied to capture the micro-topographic controls revealed by light detection and ranging (lidar) digital elevation model (lDEM) data (Le & Kumar, 2014). The goal of this paper is to present numerical scheme suited for Graphic Processing Unit (GPU) based computation to enable studies using lDEM over large areas.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability of high-resolution topographic data from lidar technique has offered new opportunities for broader exploration of the control of landscape variability at fine scales such as water and nutrient dynamics (Lefsky et al, 2002;Schwarz, 2010;Ussyshkin and Theriault, 2011;Le & Kumar, 2014) and to explore behavioral response (Kumar, 2011). Previous studies have shown that depressions arising from micro-topographic variability can have significant effects on streamflow generation (Dunne et al, 1991;Frei et al, 2010;Thompson et al, 2010;Loos and Elsenbeer, 2011), soil moisture dynamics (Simmons et al, 2011), and the surface e sub-surface flow interactions (Frei and Fleckenstein, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation